Communication breakdown: the coverage of the Robert Plant concert at Lollapalooza festival in the light of fait divers - Cruz, Fábio (2015)
Based on two articles published at the websites Portal Terra and G1, we propose a structural language study of the analytical corpus of the British singer Robert Plant’s concert with his “Sensational Space Shifters” band that happened at Lollapalooza Festival, São Paulo on March 2015. Therefore, we adopt as theoretical approach the Roland Barthes (1971) assumptions of semiotics, set in the production of meaning in the verbal level through the type of information. The research is also based on the notions of fait divers’ concept and will be conducted by the structuralist method.